Critical combinations of longitudinal and transverse direct stress for an infinitely long flat plate with edges elastically restrained against rotation - Batdorf, S. B. (Langley Memorial Aeronautical Laboratory, 1946)
A theoretical investigation was made of the buckling of an infinitely long flat plate with edges elastically restrained against rotation under combinations of longitudinal and transverse direct stress. Interaction curves are presented that give the critical combinations of stress for several different degrees of elastic edge restraint, including simple support and complete fixity. It was found that an appreciable fraction of the critical longitudinal stress may be applied to the plate without any reduction in the transverse compressive stress required for buckling.
"NACA WARTIME REPORTS are reprints of papers originally issued to provide rapid distribution of advance research results to an authorized group requiring them for the war effort. They were previously held under a security status but are now unclassified. Some of these reports were not technically edited. All have been reproduced without change in order to expedite general distribution."
"Originally issued March 1946 as Advance Restricted Report L6A05a."
"Report no. L-49."